Rigiolepis argentii (Ericaceae): a new species from Sulawesi, Indonesia - Mustaqim, Wendy Achmmad; Ardi, Wisnu Handoyo (Phytotaxa, 2021)
A new species of Rigiolepis (Ericaceae) from the island of Sulawesi, R. argentii Mustaqim & Ardi, is described. The new species is known from three locations, two in Sulawesi Selatan Province (Mount Sesean in Toraja Utara Regency and Eran Batu in Enrekang Regency) and one in Sulawesi Barat Province (Mamasa Regency). This species is similar to R. moultonii (Merr.) J.J. Sm., but differs by the persistent hairs on the abaxial surfaces of the leaves, the basal marginal glands in a shorter distance (1–2 mm) to from the petiole, bracteoles borne on the lower half of the pedicels, cup-shaped calyx tube, longer filaments (2 mm), and cupular fruits.